2022
DOI: 10.1111/acer.14902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to mother's and father's alcohol use on young children's normative perceptions of alcohol

Abstract: Background While consumption of alcohol does not often begin until early adolescence, young children are highly capable of internalizing normative information through observational learning. We used a longitudinal multiple‐informant family study to examine the impact of exposure to mothers' and fathers' drinking on young children's normative perceptions of who drinks alcohol. Methods Three hundred twenty‐nine children (4 to 6 years old at baseline [Mage 4.78 (SD = 0.725)], 51% girls) completed the Dutch electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Two studies found that children and adolescents who were more frequently exposed to parental consumption at family occasions (e.g., family barbeques) were more likely to endorse positive expectancies about alcohol such as ‘alcohol makes people more sociable’ [111, 112]. The third study found that children aged 4–6 years who were more frequently exposed to their parents' alcohol consumption were more likely than their peers to report the consumption of alcoholic beverages as being the norm for adults in social situations [113]. The fourth study demonstrated that adolescents' exposure to parental consumption increased their likelihood of later consuming alcohol themselves [114].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies found that children and adolescents who were more frequently exposed to parental consumption at family occasions (e.g., family barbeques) were more likely to endorse positive expectancies about alcohol such as ‘alcohol makes people more sociable’ [111, 112]. The third study found that children aged 4–6 years who were more frequently exposed to their parents' alcohol consumption were more likely than their peers to report the consumption of alcoholic beverages as being the norm for adults in social situations [113]. The fourth study demonstrated that adolescents' exposure to parental consumption increased their likelihood of later consuming alcohol themselves [114].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies examining the effects of children's observations of their parents' alcohol consumption were conducted in the Netherlands [111][112][113][114]. They were longitudinal studies measuring how frequently minors were exposed to their parents' drinking behaviours to see if it predicted their future expectancies, normative beliefs around alcohol use, and alcohol consumption.…”
Section: Exposure To Parents Consuming Alcoholmentioning
confidence: 99%
“…This is markedly higher than the 97 (1.6%) individuals who were ever admitted to hospital for AUDs up to the age of 40. While the current study was concerned with inpatient admissions, which probably represent more severe cases of AUDs [34], the difference between self‐reported and administratively recorded admissions for AUDs is interesting and worthy of future investigation, particularly as perceptions of what constitutes ‘normal’ drinking behaviour may differ depending upon the circumstances in which someone grew up [35].…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the influence of exposure to parental drinking on children's perception of drinking shows that what children see in their parents can be transferred to them. There is evidence of intergenerational transmission of drinking behaviour at a very young age (Cook et al, 2022). Paternal alcohol consumption is associated with an increased risk of alcohol dependence and alcohol use disorders among offspring (Thor et al, 2022).…”
Section: Discussionmentioning
confidence: 99%